HUBUNGAN SIKAP SOSIAL DAN KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR SISWA SEKOLAH DASAR DI WILAYAH KECAMATAN GUMELAR DI TINJAU DARI GENDER - Armo, Armo; Jazuli, Akhmad; Tanireja, Tukiran (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This study aims to determine the relationship between (1) social attitudes and learning achievements of fifth grade elementary school students in the Nagawiru Cluster Gumelar District; (2) emotional intelligence with learning achievement of fifth grade elementary school students; and (3) social attitudes and emotional intelligence of fifth grade elementary school students.This research used a correlational research with a quantitative approach. The variables in this study are emotional intelligence, social attitudes, and student achievement. The study population was all fifth grade students in elementary schools in the Nagawiru cluster. The number of samples taken was 75 students by using proportional random sampling technique. Data collection techniques using questionnaires and documentary studies. The analysis technique used is the product moment correlation technique and multiple regression. The results showed that (1) there was a positive and significant relationship between social attitudes with class V student achievement Whereas female students have a positive and significant relationship between social attitudes and learning achievements ; (2) there a positive and significant relationship between emotional intelligence and student achievemen especially females; and (3) there is a positive and significant relationship between social attitudes and emotional intelligence. Meanwhile, both male and female students have social attitudes with emotional intelligence with low and moderate categories.